2000
DOI: 10.1095/biolreprod62.5.1409
|View full text |Cite
|
Sign up to set email alerts
|

Male Reproductive Condition Is the Limiting Factor of Efficiency in the Male Effect During Seasonal Anestrus in Female Goats1

Abstract: Two experiments were conducted to determine whether the failure of males to induce sexual activity in goats during seasonal anestrus is due to unresponsiveness of females to male stimulus or insufficient stimulation from males. In the first study, one group of males (sexually inactive, SI; n = 4) was kept under natural photoperiod while the other (sexually active, SA; n = 4) was subjected to 2.5 mo of long days (16L:8D) and received 2 s.c. implants of melatonin. Two mo later, 2 different flocks of anovulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
3
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 24 publications
7
75
3
22
Order By: Relevance
“…Recently, we found that treatment by long days followed by melatonin implants stimulates some sexual activity in Alpine bucks under temperate latitude (Delgadillo et al, unpublished results). However, the responses of Alpine males in terms of testosterone and sexual behavior were not as strong as those observed in the subtropics in this study or with local Mexican bucks (Flores et al, 2000;Delgadillo et al, 2001). The ovarian response of anestrous light-untreated Alpine does exposed to these Alpine long days and melatonintreated bucks was limited (50% of does ovulating; Delgadillo et al, unpublished results).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Recently, we found that treatment by long days followed by melatonin implants stimulates some sexual activity in Alpine bucks under temperate latitude (Delgadillo et al, unpublished results). However, the responses of Alpine males in terms of testosterone and sexual behavior were not as strong as those observed in the subtropics in this study or with local Mexican bucks (Flores et al, 2000;Delgadillo et al, 2001). The ovarian response of anestrous light-untreated Alpine does exposed to these Alpine long days and melatonintreated bucks was limited (50% of does ovulating; Delgadillo et al, unpublished results).…”
Section: Discussioncontrasting
confidence: 57%
“…The intra-and interassay CV were 6% and 10%, respectively. Females with progesterone levels above 0.5 ng/ml were considered to have ovulated (Flores et al, 2000).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoperiod-treated males induced estrous behavior in all females (40/40) in the first 11 days after their introduction. By contrast, no behavioral activity was observed in females exposed to the light-untreated males during the same period (Flores et al, 2000). These were our first results showing that the photoperiod could be used indirectly to stimulate the sexual activity of anovulatory goats.…”
Section: Control Of the Sexual Activity Of Male And Female Goatsmentioning
confidence: 55%
“…Several factors can modify the ovulation and estrous responses of females exposed to males, including the intensity of the sexual behavior. In fact, a major limitation of the 'male effect' is that the sexual response of females is weak or absent when it is performed during mid-seasonal anestrus, probably because of the low sexual behavior of males, which are also in rest season at this time (Restall, 1992;Flores et al, 2000;Delgadillo et al, 2006). Therefore, it was tested if this limitation of the 'male effect' could be circumvented by the use of males rendered sexually active by a previous exposure to photoperiodic treatments.…”
Section: Control Of the Sexual Activity Of Male And Female Goatsmentioning
confidence: 99%